Dupuytren disease: Prevalence, treatment and outcome - Nordenskjöld, Jesper (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2019)
Purpose To study the epidemiology of Dupuytren disease and evaluate treatment outcome of collagenase injections using a modified method. Patients and methods Paper I is a register-based study. From the general population of Skåne region (1.3 million) in southern Sweden, we identified all residents aged ≥20 years who had been diagnosed with Dupuytren disease during a 16-year period and identified treatments associated with the diagnosis. Papers II-V are prospective cohort studies assessing patients with Dupuytren disease treated with collagenase injections using a modified method. Treatment indication was a palpable cord and an active extension deficit (AED) ≥20° in the metacarpophalangeal (MCP) and/or proximal interphalangeal (PIP) joint. In Paper II, 146 patients were evluated for skin tear occurrence and short-term treatment outcome. In Paper III, 187 patients were divided into 3 groups, comparing collagenase injection-related pain with or without prior local anesthesia (LA) using the the visual analog scale (VAS). In Paper IV, 86 patients were evaluated 3 years after treatment with the proportion of joints that demonstrated contracture recurrence (AED worsening ≥20°) as the primary outcome. In Paper V, 157 patients were examined by 3 hand therapists, investigating possible examiner-related difference between AED and passive extension deficit (PED) measurements. Paper VI is an ongoing randomized controlled trial of surgical fasciectomy versus collagenase injection for recurrent Dupuytren disease. Results The overall prevalence of doctor-diagnosed Dupuytren disease was 0.92%, peaking in men ≥70 years at 4.6%. 56% of diagnosed individuals underwent treatment. Skin tears, mostly minor, occurred in 40% of hands treated with collagenase injection. Greater severity of MCP joint contracture was a risk factor for skin tear. All skin tears healed with open-wound treatment, with no infections or surgical interventions required. Mean short-term contracture improvement in total AED was 55°. LA significantly reduced collagenase injection-related pain (mean VAS difference 2.1). At 3 years, complete correction (PED 0-5°) was observed in 3 of 4 MCP joints, but only in a third of PIP joints. Treatment of small finger PIP joint contractures, greater pretreatment contracture severity and previous surgical fasciectomy were significant predictors of recurrence. 70% of patients were satisfied with treatment and no adverse events were reported. The identity of the examiner was a significant determinant of the measured PED-AED difference. Conclusion Dupuytren disease is a common cause of medical consultation. Collagenase injection is a safe and effective minimally-invasive treatment method, especially for MCP joint contractures. Skin tears commonly occur during the finger manipulation procedure, but the healing prognosis is excellent. LA significantly reduces collagenase injection-related pain. Mesurement of PED may vary significantly between examiners. An ongoing randomized controlled trial will provide evidence regarding treatment of recurrent Dupuytren disease.
Keywords: Dupuytren contracture; Collagenase; Hand surgery; Dupuytren disease; Prevalence